2018
DOI: 10.1007/s00360-018-1167-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification and salinity variations on the physiology of osmoregulating and osmoconforming crustaceans

Abstract: Survival, osmoregulatory pattern, oxygen consumption, energy spent on metabolism, ammonia excretion, type of oxidized energy substrate, and hepatosomatic index were evaluated in decapods (an osmoregulating crab, Callinectes danae, and an osmoconforming seabob shrimp, Xiphopenaeus kroyeri) exposed to carbon dioxide-induced water acidification (pH 7.3, control pH 8.0) and different salinities (20, 25, 30, 35, and 40‰) for 3 days. Compared to the animals kept at controlled pH, exposure to reduced pH resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 61 publications
1
13
0
2
Order By: Relevance
“…The enhanced survival of swimming crabs under OA was expected and observed in this study, despite the lack of enhanced survival in other crabs (Ceballos-Osuna et al, 2013;Long et al, 2013a;Ragagnin et al, 2018;Ramaglia et al, 2018). Based on the SEM, crab survival was mainly explained by the carbonate system, antioxidative enzymes, seawater bacteria, gut bacteria, and digestive enzymes (Figure 7).…”
Section: Influencing Factors Of Enhanced Crab Survivalsupporting
confidence: 66%
See 1 more Smart Citation
“…The enhanced survival of swimming crabs under OA was expected and observed in this study, despite the lack of enhanced survival in other crabs (Ceballos-Osuna et al, 2013;Long et al, 2013a;Ragagnin et al, 2018;Ramaglia et al, 2018). Based on the SEM, crab survival was mainly explained by the carbonate system, antioxidative enzymes, seawater bacteria, gut bacteria, and digestive enzymes (Figure 7).…”
Section: Influencing Factors Of Enhanced Crab Survivalsupporting
confidence: 66%
“…The impacts of OA are raising increasing concerns with regard to crustaceans because of the sensitivity of calcifying animals ( Hendriks et al, 2010 ). Among them, crabs present species-specific responses to OA, such as different impacts on calcification ( Walther et al, 2010 ; Long et al, 2013a ; Wei et al, 2015 ), and survival was shown to be reduced in crabs following a longer term exposure (months) to OA, although shorter term exposure (less than 1 month) did not have any apparent effects ( Ceballos-Osuna et al, 2013 ; Long et al, 2013a ; Ragagnin et al, 2018 ; Ramaglia et al, 2018 ). In addition, OA can also induce negative effects on crab fertilization, embryonic development, and behavior ( de la Haye et al, 2011 , 2012 ; Ceballos-Osuna et al, 2013 ; Long et al, 2013b ; Dodd-Luke et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The process of actively regulating osmotic pressure needs to consume more energy stored in the crustacean to maintain normal physiological activity, the oxygen consumption and ammonia excretion rate will increase, which led to a negatively affect in growth (Ramaglia, de Castro & Augusto, ; Spanopoulos‐Hernández, Martínez‐Palacios, Vanegas‐Pérez, Rosas & Ross, ). It is now generally accepted that crustaceans have the lowest levels of metabolism when salinity is near the isotonic point, the organism can save the energy required for osmotic pressure regulation for growth (Le et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…1A). In other crab species, increases in MO 2 with declining salinity are commonly reported (Taylor et al., 1977b; Shumway, 1983; Normant and Gibowicz, 2008), although some authors have reported MO 2 increases in hypersaline waters (Ramaglia et al., 2018) or a lack of change in MO 2 with salinity (Winch and Hodgson, 2007; Theuerkauff et al., 2018). Differences between studies are likely due to diverse experimental protocols (most notably whether the measurement occurs after acute exposure or after acclimation) and differences in the osmoregulatory capacity of the test species.…”
Section: Discussionmentioning
confidence: 99%